Sequential Slot-Die Deposition of Perovskite Solar Cells Using Dimethylsulfoxide Lead Iodide Ink - Justin Searle (Materials, 2018)
This work demonstrates a sequential deposition of lead iodide followed by methylammonium iodide using the industrially compatible slot-die coating method that produces homogeneous pin-hole free films without the use of the highly toxic dimethylformamide. This is achieved through the careful selection and formulation of the solvent system and coating conditions for both the lead iodide layer and the methylammonium iodide coating. The solvent system choice is found to be critical to achieving good coating quality, conversion to the final perovskite and for the film morphology formed. A range of alcohols are assessed as solvent for methylammonium iodide formulations for use in slot-die coating. A dimethylsulfoxide solvent system for the lead iodide layer is shown which is significantly less toxic than the dimethylformamide solvent system commonly used for lead iodide deposition, which could find utility in high throughput manufacture of perovskite solar cells.